Sadomasochistic Behavior in the Perspective of Human Rights and Criminal Law - Sihabudin, Moh.; Irawan, Anang Dony (Faculty of Law, University of Muhammadiyaha Surabaya, 2023)
Sexual deviant behavior is one of the many types of crimes that exist in Indonesia. This sexual deviant behavior activity is intended to achieve sexual satisfaction in an abnormal way, one of which is sadomasochistic behavior. Sadomasochistic behavior is synonymous with sexual activity that involves violence in it, both in the form of physical violence and mental violence from their partners. In practice, sadomasochistic actors seek sexual satisfaction with certain objects that arouse their sexual desires, thereby hurting their partners. This of course refers to criminal acts of sexual violence, apart from violating criminal law provisions, sadomasochistic acts are also prohibited in Human Rights. This article was compiled to find out about sadomasochistic behavior in the perspective of Human Rights and Criminal Law based on Law Number 12 of 2022 concerning Crimes of Sexual Violence. The method used in this writing is a normative research method using the statutory approach. Then analyzed and described to solve the topics discussed in this paper. The results of the study stated that sadomasochism in husband-wife relationships is prohibited behavior. Then analyzed and described to solve the topics discussed in this paper. The results of the study stated that sadomasochism in husband-wife relationships is prohibited behavior. Then analyzed and described to solve the topics discussed in this paper. The results of the study stated that sadomasochism in husband-wife relationships is prohibited behavior